The Commodification of Considerate in Jollibeeâ€™s Commercial Break Valentine Series: Date - Lobodally, Altobeli (International Journal of Engineering and Technology, 2018)
Considerate is the most personal feeling from any human kind. Considerate can be describes as careful, not to cause inconvenience or hurt to others. For creative director in advertising field, consideration is a commodity. The creative director has been metamorphosis in symbolic way to shifting that truly feeling in a way to â€˜sellâ€™ that feeling.Â This situation has been showed in the Jollibee commercial break, especially the â€œvalentine series: dateâ€. This research is trying to disassemble how the advertiser trying to infiltrate their business in the human kind feeling â€˜sheathâ€™. To disassemble the ideology of the Jollibeeâ€™s advertisers, this research is using the Political Economy Media Theories. There are three fields in that theory. One of them is commodification. Commodification is the transformation of goods, services, ideas and people into commodities, or objects of trade. This research is using Semiotics from Roland Barthes. With three analysis level (denotation, connotation and myth) each audio and visual from Jollibee Commercial break would be dismantled. So each audio and visual from that commercial break would be considered as a sign. Which is semiotic is the science that learning about sign.